2015
DOI: 10.1136/heartjnl-2014-306703
|View full text |Cite
|
Sign up to set email alerts
|

Stress resilience and physical fitness in adolescence and risk of coronary heart disease in middle age

Abstract: ObjectivePsychosocial stress is a suggested risk for coronary heart disease (CHD). The relationship of stress resilience in adolescence with subsequent CHD risk is underinvestigated, so our objective was to assess this and investigate the possible mediating role of physical fitness.MethodsIn this register-based study, 237 980 men born between 1952 and 1956 were followed from 1987 to 2010 using information from Swedish registers. Stress resilience was measured at a compulsory military conscription examination u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
52
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 63 publications
(58 citation statements)
references
References 31 publications
4
52
0
Order By: Relevance
“…5 A Swedish study of 237 980 military conscripts (a subset of the present study cohort) found that low stress resilience was associated with a modestly increased risk of coronary heart disease, but did not examine hypertension or other risk factors for heart disease. 12 High BMI and type 2 diabetes were the strongest risk factors for hypertension in the present study. The ∼2.5-fold risk of hypertension that we observed among overweight or obese males is consistent with previously reported estimates for adult men or women.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…5 A Swedish study of 237 980 military conscripts (a subset of the present study cohort) found that low stress resilience was associated with a modestly increased risk of coronary heart disease, but did not examine hypertension or other risk factors for heart disease. 12 High BMI and type 2 diabetes were the strongest risk factors for hypertension in the present study. The ∼2.5-fold risk of hypertension that we observed among overweight or obese males is consistent with previously reported estimates for adult men or women.…”
Section: Discussionsupporting
confidence: 55%
“…11 These data have previously been used to examine stress resilience in relation to other outcomes, including coronary heart disease. 12 …”
Section: Stress Resilience Ascertainmentmentioning
confidence: 99%
“…Other studies have reported that general emotional stress [5], feelings of anger [6], hostility [7], and anxiety or depression [8, 9] are risk factors for type 2 diabetes. A Swedish study of 237,980 military conscripts (a subset of the present study cohort) found that low stress resilience was associated with a modestly increased risk of coronary heart disease, but did not examine diabetes or other risk factors for heart disease [16]. …”
Section: Discussionmentioning
confidence: 99%
“…A validation study in which 30 recorded interviews from 1972-1973 were scored by 30 psychologists reported high interrater reliability (correlation 0.86) [15]. Low stress resilience using these data has previously been examined in relation to other outcomes, including coronary heart disease [16], stroke [17] and peptic ulcer disease [18]. …”
Section: Methodsmentioning
confidence: 99%
“…Large longitudinal register-based studies have linked low stress resilience in late adolescence with subsequent increased risk of coronary heart disease,6 ischaemic and haemorrhagic stroke,7 hypertension,8 heart failure9 and diabetes mellitus type 210 as well as with liver cancer and lung cancer 11. Stress-induced unfavourable health behaviours have been proposed as a main pathway in these associations, and evidence from cross-sectional studies have indicated that higher stress resilience may mitigate tendencies for smoking, nicotine dependence, life-time alcohol consumption and illicit drug use 12–15.…”
Section: Introductionmentioning
confidence: 99%